Pengaruh Self Attribution Bias, Mental Accounting, Familiarity Bias dan Toleransi Risiko terhadap Pengambilan Keputusan Investasi - Holly, Anthony; Mardiana, Ana; Jao, Robert; Patandianan, Tripentita Loto (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
The purpose of this study was to determine some of the effects of bias, namely self-attribution bias on investment decision making, mental accounting on investment decision making, familiarity bias on investment decision making, and risk tolerance on investment decision making. The theory used is behavioral finance theory and prospect theory. This study used a purposive sampling method in selecting the sample. The sample used was students who joined the capital market study group and an investor at Atma Jaya Makassar University in the 2019-2021 class. Data collection method is done through a questionnaire. The analysis technique used is multiple linear analysis. The results of this study indicate that self-attribution bias has a positive and significant influence on investment decision making, mental accounting has a positive and significant influence on investment decision making, familiarity bias has a positive and significant influence on investment decision making, and risk tolerance has a positive and significant influence on investment decision making.